Answer:
6^6
Explanation:
The applicable rule of exponents is ...
(a^b)/(a^c) = a^(b-c)
In this problem, that means ...
(6^9)/(6^3) = 6^(9-3) = 6^6
__
It can help to remember that an exponent signifies repeated multiplication. Written out without exponents, the problem is ...
![(6\cdot6\cdot6\cdot6\cdot6\cdot6\cdot6\cdot6\cdot6)/(6\cdot6\cdot6)=6\cdot6\cdot6\cdot6\cdot6\cdot6=6^6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4uluilu2n4ztvbob1epewzi3uwg4erbwr9.png)
Note that the 3 instances of 6 in the denominator cancel 3 from the numerator. Clearly, the effect is the same as subtracting exponents.